Development of oral avian influenza virus subtypes H5 DNA vaccines using attenuated Salmonella typhimurium and silver nanoparticles as carriers - Jazayeri, Seyed Davoud (2012)
Recent epizootics of highly contagious OIE List A diseases, such as foot and mouth disease, classical swine fever and avian influenza (AI), have led to the implementation of stamping out policies resulting in the depopulation of millions of animals. In order to avoid the destruction of large numbers of animals, the possibility of pursuing different control strategies should be considered. Hence, with the advances in modern vaccine technologies, several different vaccines are currently available against AI virus (AIV) subtype H5N1. DNA vaccines are potentially safer than other traditional vaccines, such as, the whole-killed viral vaccines, are relatively inexpensive to manufacture and store, and have the potential for simultaneous immunization against multiple antigens or pathogens. Administration of DNA vaccine has been shown to stimulate immune responses, including both humoral and cellular responses. Although DNA vaccines offer several advantages, among the major setbacks are: the vaccine is unable to induce strong immunity and is not applicable for mass vaccination of poultry. Hence, there is a need to develop better delivery systems and/or adjuvants. In this study, S. typhimurium strain SV4089 and green synthesis silver nanoparticle (AgNP) were used as carriers for DNA vaccine expressing the H5 gene (pcDNA3.1/H5) of AIV A/Ck/Malaysia/5858/04 (H5N1). The safety and immunogenicity of the formulated DNA vaccines were evaluated based on cytotoxicity, humoral and cellular immune responses as well as cytokine production. Attenuated Salmonella enterica sv. typhimurium (S. typhimurium) strain SV4089 is a double mutant (Dam- and phoP-) derived from wild type S. typhimurium strain SL1344, was used as carrier for oral H5 DNA vaccine, pcDNA3.1/H5. Primary chick cells from 18 days specific-pathogen-free (SPF) embryo were used to determine the level of mRNA cytokine expression following in vitro infection with live and killed from both the attenuated and wild type S. typhimurium strains SV4089 and SL1344, respectively by using multiplex quantitative gene expression assay. Live S. typhimurium SL1344 showed strong expression of pro-inflammatory (GM-CSF, IL-1β, TGF-β, TNFSF13B, IL-12β, IL-6 and IL-8), Th1 (IFN-γ, IL-2, IL-15, IL-18) and Th2 (IL-4, IL-10) cytokines from infected primary chick cells. Although attenuated S. typhimurium SV4089 is also able to induce all the examined cytokines, the levels of expression were significantly low ranging from 1.3 to 28 fold compared to the wild type. Unlike the live wild and attenuated strains, infection of primary cells with killed strains of Salmonella associated with little or no induction of pro-inflammatory (IL-8), Th2 (IL-10, IL-4) and Th1 (IL-18) expression. pcDNA3.1/H5 was formulated using green synthesis of sliver nanoparticles (AgNP) with polyethylene glycol (PEG). The AgNP were successfully synthesized, uniformly dispersed with size in the range of 4 to 18 nm with an average size of 11 nm by using moderated temperature. Cytotoxicity of the prepared AgNP was evaluated in vitro and in vivo using MCF-7 cells and chicken splenic cytokine expression, respectively. At concentration of -5 log10 of AgNP, no cytotoxic effects were detected in MCF-7 cells with 9.5 % cell death compared to the control. One-day old SPF chicks immunized once by oral gavage with 10 μl of pcDNA3.1/H5 (2000 ng/mL) coated with 40 μl AgNP (3.7×10-2 μg of Ag) did not show any clinical manifestations. Attenuated S. typhimurium SV4089 as a potential DNA vaccine carrier in young chickens was carried out in newly hatched SPF chicks immunized once by oral gavage with 109 Salmonella colony-forming units. No deaths nor side effects were found at post-immunization with the attenuated strain. Viable bacteria were detected as soon as 3 days after inoculation by plating, fluorescent in situ hybridization (FISH) and polymerase chain reaction (PCR) from spleen, liver and cecum. Flow cytometry analysis of oral inoculated chickens against attenuated Salmonella on peripheral mononuclear blood cells (PBMC) did not show any significant responses on CD3+/CD4+ and CD3+/CD8+ cells. Regardless of the duration, immunized chickens with attenuated Salmonella strain, showed expression on IL-1β, IL-6, TNFSF13B (pro inflammatory cytokines) and IL-15, IL-18 and IL-12β (Th1 cytokine) although no significantly fold changes were recorded during 35 days experiment. Serum samples collected from the intramuscular (IM) immunized group elicited low hemagglutination-inhibition (HI) titres, while chickens immunized with attenuated S. typhimurium/pcDNA3.1/H5 and AgNP/pcDNA3.1/H5 showed rapidly increasing antibody against H5 on day 14 after immunization. The highest average antibody titres were detected on day 35 after immunization via IM, attenuated S. typhimurium/pcDNA3.1/H5 and AgNP/pcDNA3.1/H5 immunized groups, at 4.0±2.8, 51.2±7.5, and 51.2±7.5 % respectively. Attenuated S. typhimurium/pcDNA3.1/H5 and AgNP/pcDNA3.1/H5 also elicited both CD4+ and CD8+ T cells in immunized chickens as early as day 14 after immunization, at 20.5±2.0 (CD4+), 22.9±1.9 % (CD8+) and 7.5±2.0 % (CD4+), and 20±1.9 % (CD8+), respectively. Meanwhile, the CD4+ and CD8+ T cells in chickens vaccinated intramuscularly were low, at 5.9±0.9 and 8.5±1.3 %, respectively. Regardless of the duration, immunization of chickens with attenuated S.typhimurium/pcDNA3.1/H5 enhanced IL-1β, IL-6, TNFSF13B, TGF-β, IL-12β, IL-15 and IL-18 expressions although no significant differences were recorded in chickens vaccinated via IM. Immunization of chickens with AgNP/pcDNA3.1/H5 also induced similar cytokine expression profiles except for IL-6 and TNFSF13B. Although no significant differences were recorded in chickens inoculated with AgNP and AgNP/pcDNA3.1. Hence, single oral administrations of the attenuated S. typhimurium containing pcDNA3.1/H5 and AgNP/pcDNA3.1/H5 could induce strong antibody, T cell and Th1-like cytokine responses against avian influenza virus in chickens. This study provide valuable information for further study to determine the efficacy of the vaccine to induce protection against challenge with virulent H5N1 virus.